Technology and Information-Based Facility Management to Improve Academic Achievement of Inclusive Students - Lidya Puspita Sari; Agung Purwa Widiyan (Jurnal Akuntabilitas Manajemen Pendidikan, 2026)
This study aims to examine strategies for improving the learning achievement of inclusive students in utilizing information technology (IT) facilities at MAN 2 Sleman, a reference madrasah in implementing inclusive education. The background of this study is based on the fact that access for children with disabilities to digital learning in Indonesia is still limited, with only 24% having internet access (UNESCO, 2020), and 68% experiencing difficulties in online learning. The research approach used is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study show that the active involvement of students with disabilities in the digital learning process has increased significantly along with the availability of technology literacy training for teachers, the provision of adaptive IT facilities such as braille keyboards and JAWS (Job Access With Speech) screen reader applications, and the integration of learning approaches based on active and participatory learning experiences. In addition, the preparation of madrasah policies that are responsive to the individual needs of students with disabilities, such as Routine Based Interview (RBI) and the involvement of guardians, also encourage increased student participation and achievement. Field data shows an increase in average academic scores of 10–13% in the even semester of the 2024/2025 academic year among inclusive students who are actively involved in digital-based learning. The conclusion of this study states that the use of information technology in an inclusive and adaptive manner, with teacher support, equitable infrastructure, and responsive policies, contributes significantly to improving the academic achievement of students with disabilities. These findings provide important implications for madrasahs in developing more targeted operational strategies to support the transformation of digital learning that is truly friendly and fair to all students.